2010
DOI: 10.1177/0731684410366172
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harsh weather and seawater on glass fiber reinforced epoxy composite

Abstract: The lack of reliable engineering data on the durability of glass fiber reinforced Epoxy (GFRE) pipes when exposed to harsh Arabian Gulf outdoor environment has limited their wide use for saltwater and crude oil handling and transportation. This article explores the combined effect of natural and accelerated weathering and seawater on tensile properties of GFRE pipe materials. Saltwater filled pipes were exposed to outdoor environment in Dhahran, Saudi Arabia for periods ranging from 6 to 12 months. Ring-shaped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Figure 4 shows the weight gain for epoxy samples conditioned at 40°C, and indicates that the [0] 2 samples are approaching an equilibrium moisture content at 1000 hours. However, the thicker samples [0] 6 have lower moisture absorption and have not reached saturation. Initial testing protocol was to remove sample after 1000 hrs at 40°C and store in synthetic sea water at…”
Section: Chemical Analysis Of Soaked Samplesmentioning
confidence: 99%
“…Figure 4 shows the weight gain for epoxy samples conditioned at 40°C, and indicates that the [0] 2 samples are approaching an equilibrium moisture content at 1000 hours. However, the thicker samples [0] 6 have lower moisture absorption and have not reached saturation. Initial testing protocol was to remove sample after 1000 hrs at 40°C and store in synthetic sea water at…”
Section: Chemical Analysis Of Soaked Samplesmentioning
confidence: 99%
“…However, the most possible cause of deterioration of the K-HDPE composite was due to the effect of high humidity produced from water vapour inside the accelerated weathering chamber. Hydrophilic kenaf fibres attract water molecules into the K-HDPE composite and cause fibre-matrix debonding (Merah et al, 2010). As the exposure time increases, the moisture creeps deeper into the K-HDPE composite creating more fibre-matrix debonding, which decreases the tensile strength of the composites (Figure 6).…”
Section: Methodsmentioning
confidence: 99%
“…One major advantage of kenaf fibres for biocomposites is that it has the appearance of wood but possesses plastic processing properties, which means it can easily be fabricated like other plastic products. These so-called environmentally friendly composite materials have been developed into numerous applications both for indoor and outdoor use (Misri, Leman, Sapuan, & Ishak, 2010;Maleque, Belal, & Sapuan, 2007;Merah, Nizamuddin, Khan, Al-Sulaiman, & Mehdi, 2010;Rowell & Stout, 2007). However, biocomposite materials intended for outdoor applications are exposed to weather elements that deteriorate the integrity of the composite's mechanical properties (Maleque et al, 2007;Merah et al, 2010;Pritchard, 2000;Brennan & Fedor, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, epoxy resin is one of the most applied thermoset polymers as a matrix for glass fiber reinforced pipes (GFRP) and anticorrosion coatings. However, it is observed that liquid uptake degrades the functional, structural, and mechanical properties of epoxy‐based composites . Water absorption in polymer structures is related to the existence of molecule‐size holes and the affinity between polar groups of polymers and water .…”
Section: Introductionmentioning
confidence: 99%